2016
DOI: 10.3402/gha.v9.29247
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in HIV knowledge and attitudes among Vietnamese women based on the Multiple Indicator Cluster Surveys, 2000, 2006, and 2011: what do we know and what should we do to protect them?

Abstract: BackgroundIn Vietnam, women are at risk of HIV infection due to many factors. However, there is limited evidence about what women know and how they behave to protect themselves from HIV.ObjectiveThe objective of this study was to investigate the trends in comprehensive HIV/AIDS knowledge, attitude, and associated factors among Vietnamese women from 2000 to 2011.DesignData from three waves of the Vietnam Multiple Indicator Cluster Surveys (years 2000, 2006, and 2011) were used. Logistic regression methods exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
23
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 19 publications
16
23
2
1
Order By: Relevance
“…Thus, we would interpret our finding with caution and would recommend in-depth analysis regarding the effect of religion on the knowledge about HIV/AIDS among the women in Bangladesh. This study results show that women from a higher level of socio-economic status (middle and rich) have a higher likelihood of HIV/AIDS knowledge compared to poor women, which is consistent with the studies [30]. The justification of the result is that women from upper socio-economic class have more access to modern amenities and health care facilities, which increase their likelihood of knowing about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, we would interpret our finding with caution and would recommend in-depth analysis regarding the effect of religion on the knowledge about HIV/AIDS among the women in Bangladesh. This study results show that women from a higher level of socio-economic status (middle and rich) have a higher likelihood of HIV/AIDS knowledge compared to poor women, which is consistent with the studies [30]. The justification of the result is that women from upper socio-economic class have more access to modern amenities and health care facilities, which increase their likelihood of knowing about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, women living in urban areas are more likely to have knowledge about HIV/AIDS compared to rural women, which is in accordance with other studies [10, 21, 30, 32]. Contrary to our findings, there are few studies [17], which reported that the type of residence is unrelated to women’s knowledge about HIV/AIDS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings are in conformity with the study conducted among Vietnamese women which reported that married women had less odds of having comprehensive knowledge of HIV compared to singles because they believe that marriage is a protection to risky sexual behaviors. 15 Women in rural areas (OR=0.91) 95% CI (0.77-1.09) had lower odds of having comprehensive knowledge compared to urban women in this study. This result correlates with several findings.…”
Section: Discussionmentioning
confidence: 50%
“…In this study, majority of the respondents (24%) were in the age group of (15)(16)(17)(18)(19) and a high proportion of women (80%) resided in rural areas. Catholic religion had majority of the respondents (40%) compared to other religions.…”
Section: Resultsmentioning
confidence: 66%